Approaches to head movement: A critical assessment. Issue 1 (24th May 2018) - Dékány, Éva
Abstract : Heads can be spelled out higher than their merge-in position. The operation that the transformationalist generative literature uses to model this is called head movement. Government and Binding posited that the operation in question involves adjunction of a lower head to a higher head in narrow syntax. It has been noted early on, however, that this approach is highly problematic because head-adjunction violates several well-motivated constraints on syntactic structures. This overview article surveys the problems raised by the adjunction approach as well as the recent alternative analyses that were suggested in its stead in the Minimalist program. It evaluates the strengths and weaknesses of the alternatives, discusses to what extent they are able to eliminate the problems raised by the adjunction analysis, and also points out the new problems that they give rise to.